Using Environmental Perception and Local Knowledge to improve the effectiveness of an Urban Park in Northeast Brazil - Junior, Valdecir da Silva; Santos, Bráulio Almeida (Ethnobiology and Conservation, 2017)
The Xem-Xem Forest State Park (Parque Estadual da Mata do Xém-Xém) is a 182-ha Atlantic forest remnant located in the metropolitan region of João Pessoa, Paraíba, Northeast Brazil. Since its legal creation in 2000, it has been facing several management problems and social conflicts that jointly has reduced its effectiveness. In this study we examined the environmental perception of residents surrounding the Park and the staff of the Paraíba state environmental agency (SUDEMA) in order to clearly identify those problems and conflicts and provide possible solutions. Semi structured interviews with both residents (n = 29) and staff members (n = 4) revealed that the Park is clearly valuable as a repository of biodiversity and a place for leisure and recreation, highlighting its great socioecological function. These benefits, however, were impaired or hindered mainly by fear of violence, lack of infrastructure, extremely limited staff and virtual absence of administrative structure. Furthermore, the protective measures of the Park were considered incipient and did not match the expectations and needs of local communities. We urgently recommend (1) the creation of the Park’s management council, (2) the development of its management plan, (3) the implementation of public policies surrounding the area to ameliorate conditions for public use and improve biodiversity protection and (4) the continuity of ethnographic researches focusing on the relationship between local communities and the Park.